Draft Fifth Five Year Plan of Andaman and Nicobar Islands Volume V - Planning Commission (Planning Commission, 1974)
At present this Administration is having only a Small Statistical Bureau with skeleton staff. It is not possible for this Bureau to collect all relevant data concerning the islands economy and as such planning future developmental programmes in the proper perspective has become difficult. It is, therefore, proposed to establish a full-fledged Directorate of Statistics under a Class I Officer with necessary compliment of staff during the Fifth Plan. The Director will supervise and coordinate the works relating to State Income Unit, Sample Survey and Census Unit, vital Statistics Unit, Departmental statistical cells, Monitoring Cell, Housing cells etc.
Andaman and Nicobar Administration
Andaman and Nicobar Administration